Plant Tissue Culture Engineering - Dutta Gupta, S.; Ibaraki, Yasuomi (Focus on Biotechnology, 2008)
It is my privilege to contribute the foreword for this unique volume entitled: "Plant Tissue Culture Engineering," edited by S. Dutta Gupta and Y. Ibaraki. While there have been a number of volumes published regarding the basic methods and applications of plant tissue and cell culture technologies, and even considerable attention provided to bioreactor design, relatively little attention has been afforded to the engineering principles that have emerged as critical contributions to the commercial applications of plant biotechnologies. This volume, "Plant Tissue Culture Engineering," signals a turning point: the recognition that this specialized field of plant science must be integrated with engineering principles in order to develop efficient, cost effective, and large scale applications of these technologies. I am most impressed with the organization of this volume, and the extensive list of chapters contributed by expert authors from around the world who are leading the emergence of this interdisciplinary enterprise. The editors are to be commended for their skilful crafting of this important volume. The first two parts provide the basic information that is relevant to the field as a whole, the following two parts elaborate on these principles, and the last part elaborates on specific technologies or applications.